THE STUDY OF ARTICULATORY PHONETICS AND ITS ROLE IN LANGUAGE LEARNING (International journal of artificial intelligence, 2024)
Articulatory phonetics, a branch of phonetics that studies the physiological mechanisms involved in speech sound generation, offers fundamental insights into human communication. This article investigates the mechanisms of speech production, focusing on the role of speech organs, articulatory processes, and their importance in language learning. Understanding how sounds are generated and modified can help learners and instructors improve their pronunciation and intelligibility. The uses of articulatory phonetics in technology, speech therapy, and linguistic study are all covered.